Nanodrugs systems for therapy and diagnosis of esophageal cancer - Zhang, Lihan; Li, Xing; Yue, Guangxing; Guo, Lihao; Hu, Yanhui; Cui, Qingli; Wang, Jia; Tang, Jingwen; Liu, Huaimin (Frontiers in Bioengineering and Biotechnology, 2023)
With the increasing incidence of esophageal cancer, its diagnosis and treatment have become one of the key issues in medical research today. However, the current diagnostic and treatment methods face many unresolved issues, such as low accuracy of early diagnosis, painful treatment process for patients, and high recurrence rate after recovery. Therefore, new methods for the diagnosis and treatment of esophageal cancer need to be further explored, and the rapid development of nanomaterials has brought new ideas for solving this problem. Nanomaterials used as drugs or drug delivery systems possess several advantages, such as high drug capacity, adjustably specific targeting capability, and stable structure, which endow nanomaterials great application potential in cancer therapy. However, even though the nanomaterials have been widely used in cancer therapy, there are still few reviews on their application in esophageal cancer, and systematical overview and analysis are deficient. Herein, we overviewed the application of nanodrug systems in therapy and diagnosis of esophageal cancer and summarized some representative case of their application in diagnosis, chemotherapy, targeted drug, radiotherapy, immunity, surgery and new therapeutic method of esophageal cancer. In addition, the nanomaterials used for therapy of esophageal cancer complications, esophageal stenosis or obstruction and oesophagitis, are also listed here. Finally, the challenge and the future of nanomaterials used in cancer therapy were discussed.